DINAMIKA PENETAPAN PENJABAT SEMENTARA (PJS) KEPALA DESA PAUH KECAMATAN BONAI DARUSSALAM KABUPATEN ROKAN HULU TAHUN 2012-2014 - Riandy Ersa Ersa; Wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The enactment of Law No. 32 Year 2004 on Regional Government as a form of refinement of the Act No. 22 of 1999 that is considered still has many weaknesses . In Act No. 32 of 2004 there was no change to the establishment of village head but there is a change to the term of office . For the determination of village head is fixed directly elected by the villagers in Article 25 ( 5 ) , and under section 91 ( 3 ) for a term of six years and the Chief can only be re-elected for one more next term. Based on legislation applicable and the determination of the true term should refer to the village chief or guided by the existing regulations . However, an interesting phenomenon to be studied , that the village Pauh subdistrict Bonai Darussalam Rokan Hulu province of Law No. 32 of 2004 for the establishment and tenure of village head is not enforced . This research was conducted in the village of Bonai Darussalam Pauh subdistrict Rokan Hulu , which is the key informants in this study is Agusman as acting interim ( PJS ) Pauh village and BPD. In doing this data collection , the data obtained from in-depth interviews to the informant . Once the data is collected and then analyzed using qualitative descriptive analysis . From the results of this study concluded that the inconsistent Consultative Body (BPD ) Pauh in exercising its functions and powers as well as the interest by certain parties , and also village Pauh less given serious consideration by the District and the Local Government of Rokan Hulu .Keywords: Implementation of Policies, Political Interests, Leadership, Power.